MASSIVE PULMONARY EMBOLISM IN OLDER PATIENT: SURVIVAL DESPITE STATISTIC DATA - Makharynska, O. S.; Doroshenko, O. V.; Rahul, M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Massive pulmonary thromboembolism is presented in this article on example of clinical case. Clinical investigation, prognosis evaluation tools, diagnosis and acute phase treatment along with prevention of recurrent episode of pulmonary embolism presented. Observed and described clinical case of pulmonary embolism in older patient, when patient was mistakenly diagnosed in emergency department as acute coronary syndrome patient. Not every case in medical practice are clearly understandable from the first view, but in the case of diagnostic difficulties, attention should be paid to the possible presence of the main risk factors for thromboembolic complications, the auscultators pattern in the lungs, and the possibility of developing PE (usage of widely unknown prognostic scales makes the task of physician easier and diagnosis evaluation more clear) in each clinical case.